2008
DOI: 10.1002/anie.200703272
|View full text |Cite
|
Sign up to set email alerts
|

Outer‐Sphere Coordination Chemistry: Selective Extraction and Transport of the [PtCl6]2− Anion

Abstract: What's on the outside? Selective extraction and transport of [PtCl6]2− from aqueous acidic solutions in the presence of excess chloride has been demonstrated through outer‐sphere coordination of the metalloanion by tripodal polyamide and polyurea receptors (see picture; Pt purple, N blue, O red, Cl green). Loading and stripping of the organic phase can be controlled by variation of the pH value of the aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 31 publications
2
41
0
1
Order By: Relevance
“…Outer-sphere interactions between the Ru complex anion and the protonated ligands can contribute the formation of stable Ru complex in the organic phase as in the previous study regarding Pt(IV) extractions [26]. …”
Section: Structural Study Of Ru Extracted By Ehbaamentioning
confidence: 64%
“…Outer-sphere interactions between the Ru complex anion and the protonated ligands can contribute the formation of stable Ru complex in the organic phase as in the previous study regarding Pt(IV) extractions [26]. …”
Section: Structural Study Of Ru Extracted By Ehbaamentioning
confidence: 64%
“…By increasing the extraction time up to 24 h, E% of Pt(IV) increases moderately because of the additional effect of a multidentate ligand of 1. The reason for the increased E% may be as follows: the native diethylamino group of 1 might interact with the Pt(IV) ions via inner-sphere substitution processes (30). Now, we focus on the structural mode of coordination with Pt ions, in order to clarify the extraction mechanism.…”
Section: Mechanism Of Pt(iv) Extractionmentioning
confidence: 99%
“…For example, organic-inorganic layered perovskites that exhibit interesting electrical (semiconducting) [11] and optical [12] properties have been synthesized [13]. Magnetic [14] and nonlinear optical [15] hybrid materials have also been designed exploiting the nucleophilic character of perhalometallates, and the judicious design of a multiple hydrogen-bond donor ligand which can encapsulate perhalometallates has been employed for the recovery of metal salts [16]. Recently, some studies on hydrogen bonded salts have demonstrated that N-H···X-M hydrogen bonds permit the formation of N-M bonds in the solid state by the elimination of gaseous HX, which will be discussed in detail in Section 5.4.5 [17,18].…”
Section: Halogens As Nucleophilesmentioning
confidence: 99%